Flavanol-Rich Cacao Mucilage Juice Enhances Recovery of Power but Not Strength from Intensive Exercise in Healthy, Young Men - Paul T. Morgan; Paola M. Wollman; Sarah R. Jackman; Joanna L. Bowtell (Sports, 2018)
(1) Background: Mucilage within cacao pods contains high levels of polyphenols. We investigated whether consumption of cacao juice enhances the recovery of muscle function following intensive knee extension exercise. (2) Methods: Ten recreationally active males completed two trials of 10 sets of 10 single leg knee extensions at ~80% one repetition maximum. Participants consumed each supplement (ZumoCacao® juice, CJ or a dextrose drink, PL) for 7 days prior to and 48 h post exercise. Knee extension maximum voluntary contraction (MVC) and a counter movement jump (CMJ) were performed at baseline, immediately, 24 h, and 48 h post-exercise. Venous blood samples were collected at each time point and analyzed for indices of inflammation, oxidative damage, and muscle damage. (3) Results: CMJ height recovered faster with CJ at 24 h and 48 h post-exercise (p < 0.05), but there was no effect of CJ on recovery of MVC (both p > 0.05). There was also no effect of the trial on any blood markers (all p > 0.05). (4) Conclusions: Supplementation with CJ for 7 days prior to and 2 days after intensive knee extensor exercise improved functional recovery as shown by an improved recovery of CMJ up to 48 h post-exercise. However, the precise mechanism of action is unclear and requires further investigation.